2009
DOI: 10.1093/nar/gkp067
|View full text |Cite
|
Sign up to set email alerts
|

HMGB1 and HMGB2 proteins up-regulate cellular expression of human topoisomerase II 

Abstract: Topoisomerase IIα (topo IIα) is a nuclear enzyme involved in several critical processes, including chromosome replication, segregation and recombination. Previously we have shown that chromosomal protein HMGB1 interacts with topo IIα, and stimulates its catalytic activity. Here we show the effect of HMGB1 on the activity of the human topo IIα gene promoter in different cell lines. We demonstrate that HMGB1, but not a mutant of HMGB1 incapable of DNA bending, up-regulates the activity of the topo IIα promoter i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 72 publications
(149 reference statements)
1
36
0
2
Order By: Relevance
“…In this study, we confirmed the up-regulation of HMGB1 in the NM fraction of chromosomal instable CRC and show, that besides HMGB1, HMGB2 and HMGB3 were also specifically up-regulated in the CINϩ CRC samples with HMGB3 up-regulation also being reflected at the mRNA level. HMGB1/2 have been implicated in cellular response to chemotherapy-induced DNA damage (39) and can up-regulate topoisomerase II (40), providing a possible link to chromosomal instability. Indeed, overexpression of HMGB1 induced unbalanced chromosomal rearrangements in human prostate cancer cell lines (41).…”
Section: Chromosomal Instabilitymentioning
confidence: 99%
“…In this study, we confirmed the up-regulation of HMGB1 in the NM fraction of chromosomal instable CRC and show, that besides HMGB1, HMGB2 and HMGB3 were also specifically up-regulated in the CINϩ CRC samples with HMGB3 up-regulation also being reflected at the mRNA level. HMGB1/2 have been implicated in cellular response to chemotherapy-induced DNA damage (39) and can up-regulate topoisomerase II (40), providing a possible link to chromosomal instability. Indeed, overexpression of HMGB1 induced unbalanced chromosomal rearrangements in human prostate cancer cell lines (41).…”
Section: Chromosomal Instabilitymentioning
confidence: 99%
“…Indeed, HMGB2 was described as binding to DNA without any sequence specificity but potentiating the activity of other transcription factors such as Oct-1 22 and NF-Y. 23 We thus investigated whether Oct-1, NF-YA, and HMGB2 associated with sites 1 and 2 at the GFI1B promoter in primary erythroid cells. CD34 ϩ cells were isolated from cord blood and amplified in a 2-phase culture system: a 5-day amplification step (D1-D5) in the presence of SCF, IL-3, EPO, and dexamethasone followed by a 5-day differentiation step (E0-E5) in the presence of SCF and EPO.…”
Section: Hmgb2 Is Required For Erythroid Differentiation 689mentioning
confidence: 99%
“…18,19 In addition, HMGB proteins were also shown to interact with transcription factors such as p53, 20 HoxD9, 21 Oct-1/2, 22 and NF-Y. 23 These interactions eventually lead to the recruitment of HMGB to specific sites of the genome where it locally modulates the association of transcription factors to their cognate DNA-binding sites.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, increased HMGB2 levels h, like HHMGB1, facilitates efficient nonviral gene delivery (Sloots and Wels, 2005), which may be useful for gene therapy (Balani et al, 2009). Overexpression of HMGB2 increases topoisomerase II alpha expression (Stros et al, 2009) and correlates with the progression of several tumors such as skin, liver, and bladder cancer (Kwon et al, 2010a; Sharma et al, 2008; Wang et al, 2013j). Like HMGB1, HMGB2 is secreted by myeloid cells and has mitogenic and chemoattractant functions by binding to RAGE (Pusterla et al, 2009).…”
Section: Introduction and Historical Backgroundmentioning
confidence: 99%